Fractionation of phosphorus in soils with different geological and soil physicochemical properties in southern Tanzania. Issue 3 (4th May 2018) - Nishigaki, Tomohiro; Sugihara, Soh; Kobayashi, Kazuki; Hashimoto, Yohey; Kilasara, Method; Tanaka, Haruo; Watanabe, Tetsuhiro; Funakawa, Shinya
ABSTRACT: Soil phosphorus (P) forms have been practically defined as chemically fractionated pools. A knowledge of the abundance and diversity of P forms in soil, and the factors affecting them, will lead to better soil management. However, little is known about the differences in P forms among soils with different geological properties in tropical Africa. The aim of this study was to investigate the P forms in soils with different physicochemical properties formed under different geological conditions in southern Tanzania and to identify the factors affecting the P forms in these soils. In total, 37 surface soil samples were collected from three geological groups; the plutonic (mainly granite) rock (PL) group, the sedimentary and metamorphic rock (SM) group, and the volcanic ash (V) group. Soil P was sequentially extracted by NH4 Cl, NH4 F, NaHCO3, NaOH + NaCl, and HCl, and inorganic (Pi ) and organic P (Po ) in each fraction were determined. The lowest total P was in the PL group (average, 360 mg P kg -1 ) because of the high sand content. Iron (Fe)-P (NaOH-Pi ) was the major form in this group, accounting for 8.4% of total P. In the SM group (average total P, 860 mg P kg -1 ), Fe-P was the major form in most, accounting for 7.8% of total P. Soils in the SM group occasionally had high calcium (Ca)-P due to application of chemical fertilizer at the collection site. The V group had the highest total P (average, 1600 mg P kg -1 ) and its major P form was Ca-P, which was possibly derived from primary minerals (i.e., apatite), accounting for 14% of total P. In addition, the high oxalate-extractable Al possibly caused the accumulation of Al-P in the V group. Oxalate-extractable Fe generally increased with increasing Fe-Pi, while oxalate-extractable Al increased with increasing organic P and Al-Pi in soils in all three geological groups. These results demonstrate that the soil P forms differ greatly among sites in southern Tanzania with different geological conditions and associated soil properties.